Serum valeric acid stimulates lung epithelial cilia assembly and improves prognosis in patients with severe respiratory infections - Zhang, Yabin; Zhang, Yuqing; Wang, Lin; Liu, Beibei; Zheng, Jiajia; Cao, Jiabao; Xie, Lixin; Shen, Ning; Wang, Jun (Frontiers in Pharmacology, 2026)
IntroductionGlobally, respiratory infections remain a leading cause of mortality, with treatment efficacy increasingly challenged by antimicrobial resistance. This study aimed to investigate the role of serum metabolites in the prognosis of severe human pneumonia.MethodsUntargeted and targeted serum metabolomics were performed on intensive care unit (ICU) patients. Experimental validation was conducted in a murine bacterial infection model and cellular models. RNA sequencing was used for mechanistic exploration to identify the signaling pathways regulated by the key metabolite.ResultsValeric acid, a short-chain fatty acid, was significantly elevated in survivors compared with non-survivors of severe pneumonia. In the murine Klebsiella pneumoniae model, valeric acid treatment alleviated infection severity, reduced body weight loss, lung inflammation, and bacterial load. Mechanistically, RNA sequencing revealed that valeric acid suppresses IL-17-associated inflammation and upregulates pathways related to mucociliary clearance. We further delineated the underlying mechanism, finding that valeric acid acts as a histone deacetylase (HDAC) inhibitor, specifically targeting HDAC3. This inhibition activates the canonical Wnt/β-catenin signaling pathway, leading to the upregulation of the master transcriptional regulator Foxj1 and subsequent promotion of cilia assembly and function in airway epithelia.DiscussionThe findings establish a protective role for the gut microbiome-derived valeric acid in respiratory infections via the novel HDAC-Wnt-FOXJ1 axis, revealing its potential as a therapeutic agent to improve clinical outcomes.